2021
DOI: 10.3390/applmicrobiol1020021
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phage Cocktail for Improving the Overall Microbiological Quality of Sprouts—Two Methods of Application

Abstract: Background: the aim of this study was to improve the overall microbiological quality of five different sprouts (alfalfa, kale, lentil, sunflower, radish) using newly isolated bacteriophages. Method: in this study we had isolated from sewage 18 bacteriophages targeting bacteria dominant in sprouts. Five selected bacteriophage strains were photographed using a transmission electron microscope (TEM), and we analyzed the rate of attachment, resistance to chloroform, the burst size, and the latency period. Two meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…In recent years, great attention has been paid to biological methods of food preservation [22,23]. Recently, there has been growing interest in the use of lytic bacteriophages as an innovative bio-preservative of fresh and minimally processed food products that can inhibit the growth of food-borne pathogens and spoilage microorganisms [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great attention has been paid to biological methods of food preservation [22,23]. Recently, there has been growing interest in the use of lytic bacteriophages as an innovative bio-preservative of fresh and minimally processed food products that can inhibit the growth of food-borne pathogens and spoilage microorganisms [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies available that assess the microbiological quality of minimally processed plant products. An assessment of microbiological quality of sprouts carried out by Gientka et al (2021) showed that the most microbiologically contaminated were alfalfa sprouts (TNB = 8.14 log CFU/g). In other studies (Berthold-Pluta et al, 2017), the total count of aerobic mesophilic bacteria in samples of lettuces, sprouts and non-pasteurized fruit, vegetable and fruitvegetable juices was in the range of 5.6-7.6, 6.7-8.4 and 2.9-7.7 log CFU/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We found only one study in which the effect of adding a bacteriophage suspension on the level of TNB was tested. In the experiment of Gientka et al (2021), similarly to this article, various methods for applying phage suspensions were used. The spraying method was significantly more efficient on sprouts than a pad soaked with phage, and the maximum reduction effect after 48 h of incubation was 1.5 log CFU/g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations